laminate

JP2025029776APending Publication Date: 2025-03-07MITSUI CHEMICALS INC

Patent Information

Application Number
JP2023134591
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0018】 本発明の一実施形態によれば、易印刷性、ヒートシール性、および耐熱性に優れ、ヒートシール後の外観にシワが生じにくい積層体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029776000001
    Figure 2025029776000001
  • Figure 2025029776000002
    Figure 2025029776000002
  • Figure 2025029776000003
    Figure 2025029776000003
Patent Text Reader

Abstract

To provide a laminate which has excellent printability, heat sealability and heat resistance and hardly causes wrinkles on appearance after heat sealing.SOLUTION: There is provided a laminate which has a layer (I) containing a thermoplastic resin, a resin layer (II) containing a 4-methyl-1-pentene-based polymer (A) satisfying following requirements (A) to (c) and a layer (III) containing a thermoplastic resin in a thickness direction in this order: (a) a melting point (Tm) measured by a differential scanning calorimeter (DSC) is 180 to 220°C, (b) an endothermic end temperature (TmE) in a melting (endothermic) curve measured by DSC is 230°C or less and (c) an exothermic start temperature (TcS) in the crystallization (exothermic) curve measured by DSC is 210°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate. [Background technology]

[0002] In recent years, against the backdrop of an increase in marine plastic waste worldwide, there is a need to promote the trend toward recycling used plastic packaging materials. For this reason, it is expected that packaging materials that are normally composed of multiple different materials will be converted into mono-material packaging materials composed of a single material such as polyolefin.

[0003] Films formed from thermoplastic resins such as polyolefin-based resins are widely used as packaging materials for foods and the like because they have excellent printability, flexibility, transparency, and heat sealability (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2007 / 015415 Summary of the Invention [Problem to be solved by the invention]

[0005] However, conventionally, films formed from thermoplastic resins such as polyolefin resins have room for further improvement in view of the tendency of wrinkles to appear on the outer surface after heat sealing. Therefore, an object of the present invention is to provide a laminate which is excellent in printability, heat sealability and heat resistance, and which is less susceptible to wrinkles in appearance after heat sealing. [Means for solving the problem]

[0006] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by a laminate having a layer (I) containing a thermoplastic resin, a resin layer (II) containing a 4-methyl-1-pentene polymer (A) satisfying specific requirements, and a layer (III) containing a thermoplastic resin, and have thus completed the present invention.

[0007] That is, the means for solving the above problems include the following aspects. [1] A layer (I) containing a thermoplastic resin; A resin layer (II) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirements (a) to (c); A layer (III) containing a thermoplastic resin; A laminate having the above in this order in the thickness direction. (a) The melting point (Tm) measured by differential scanning calorimetry (DSC) is 180 to 220°C. (b) The endothermic end temperature (TmE) in the melting (endothermic) curve measured by DSC is 230°C or lower. (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by DSC is 210°C or lower.

[0008] [2] The laminate according to [1], wherein the layer (II) has a first surface and a second surface, the layer (I) is provided in contact with the first surface of the layer (II), and the layer (III) is provided in contact with the second surface of the layer (II).

[0009] [3] The laminate according to [1] or [2], wherein the layer (I) and the layer (III) contain a polyolefin having a melting point of 200° C. or less as measured by a differential scanning calorimeter (DSC).

[0010] [4] The laminate according to [3], wherein the polyolefin having a melting point of 200° C. or less is at least one resin selected from the group consisting of polypropylene and polyethylene.

[0011] [5] The laminate according to any one of [1] to [4], wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. in the range of 0.5 to 6.0 dL / g.

[0012] [6] In the 4-methyl-1-pentene polymer (A), the amount of structural units (U1) derived from 4-methyl-1-pentene is 84 to 100 mol %, The laminate according to any one of [1] to [5], wherein the total amount (U2) of structural units derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0 to 16 mol % (wherein the sum of U1 and U2 is 100 mol %).

[0013] [7] The laminate according to [6], wherein the α-olefin is an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).

[0014] [8] The laminate according to any one of [1] to [7], wherein the resin layer (II) has a thickness of 50 μm or less.

[0015] [9] The laminate according to any one of [1] to [8], wherein the 4-methyl-1-pentene polymer (A) is modified.

[0016]

[10] The laminate according to [9], wherein the 4-methyl-1-pentene polymer (A) is a graft-modified polymer, and the amount of graft modification is 0.1 to 5.0% by mass.

[0017]

[11] The laminate according to any one of [1] to

[10] , wherein the resin layer (II) further contains an isocyanate compound (B). Effect of the Invention

[0018] According to one embodiment of the present invention, it is possible to provide a laminate that is excellent in printability, heat sealability, and heat resistance, and is less likely to develop wrinkles in appearance after heat sealing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Laminate> The laminate of the present invention has, in the thickness direction, a layer (I) containing a thermoplastic resin, a resin layer (II) containing a 4-methyl-1-pentene polymer (A) satisfying the requirements (a) to (c), and a layer (III) containing a thermoplastic resin in this order. Each of the components of the laminate of the present invention will be described below. The various monomers in the present disclosure may be derived from fossil raw materials or biomass.

[0020] <Resin layer (II)> [4-Methyl-1-pentene polymer (A)] The 4-methyl-1-pentene polymer (A) contained in the resin layer (II) satisfies the following requirements (a) to (c). In the following description, a structural unit derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) may be referred to as a "structural unit (i)". Similarly, a structural unit derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) in the 4-methyl-1-pentene polymer (A) may be referred to as a "structural unit (ii)".

[0021] [Requirement (a)] The melting point (Tm) measured by a differential scanning calorimeter (DSC) by the method described in the Examples below is 180° C. to 220° C., preferably 184 to 217° C., and more preferably 188 to 215° C. When the melting point (Tm) measured by a differential scanning calorimeter (DSC) is within the above range, the heat resistance of the resin layer (II) containing the 4-methyl-1-pentene polymer (A) is good, and the laminate of the present invention has excellent appearance after heat sealing. The melting point (Tm) value tends to depend on the stereoregularity of the 4-methyl-1-pentene polymer (A) and the content of the structural unit (ii) in the 4-methyl-1-pentene polymer (A). Therefore, the melting point (Tm) can be adjusted by using an olefin polymerization catalyst described later and further controlling the content of the structural unit (ii).

[0022] [Requirement (b)] The endothermic end temperature (TmE) in the melting (endothermic) curve measured by a differential scanning calorimeter (DSC) according to the method described in the Examples below is 230° C. or lower, preferably less than 230° C., more preferably less than 228° C., and even more preferably less than 228° C. Here, the endothermic end temperature means the temperature at which melting is completed. The endothermic end temperature and the exothermic start temperature described below are indexes different from the onset and offset, which are generally the intersection points between the baseline and the tangent to the steady line. The endothermic end temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) or by controlling the content of the structural unit (ii).

[0023] The 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range is excellent in heat resistance. Therefore, the resin layer formed from the coating agent obtained from the composition containing the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range also tends to be excellent in heat resistance, and the laminate of the present invention has excellent appearance after heat sealing. In addition, the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range is more easily dissolved in a solvent that can be used in preparing the coating agent than a 4-methyl-1-pentene polymer having an endothermic end temperature not in the above range. Therefore, the properties of the coating agent prepared using the 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range tend to be uniform.

[0024] [Requirement (c)] The exothermic onset temperature (TcS) in the crystallization (exothermic) curve measured by a differential scanning calorimeter (DSC) according to the method described in the Examples below is 210°C or lower, preferably less than 210°C, more preferably 200°C or lower, and even more preferably less than 200°C. The heat generation initiation temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) and by controlling the content of the structural unit (ii).

[0025] The 4-methyl-1-pentene polymer (A) having a heat generation initiation temperature within the above range is excellent in heat resistance. Therefore, the resin layer formed from the coating agent obtained from the composition containing the 4-methyl-1-pentene polymer (A) having a heat generation initiation temperature within the above range also tends to be excellent in heat resistance, and the laminate of the present invention has excellent appearance after heat sealing. In addition, the 4-methyl-1-pentene polymer (A) having a heat generation initiation temperature within the above range is more easily dissolved in a solvent that can be used when preparing the coating agent than a 4-methyl-1-pentene polymer having a heat generation initiation temperature outside the above range. Therefore, the properties of the coating agent prepared using the 4-methyl-1-pentene polymer (A) having a heat generation initiation temperature within the above range tend to be uniform.

[0026] The 4-methyl-1-pentene polymer (A) used in the laminate of the present invention satisfies the requirements (a) to (c), and therefore has excellent solubility in a solvent while maintaining heat resistance. In addition, the 4-methyl-1-pentene polymer (A) that satisfies the requirements (a) to (c) has excellent solubility in a solvent, and therefore is likely to remain dissolved in the solvent. Therefore, the 4-methyl-1-pentene polymer (A) that satisfies the requirements (a) to (c) has good storage stability when dissolved in a solvent, compared with a 4-methyl-1-pentene polymer that does not satisfy one or more of the requirements (a) to (c).

[0027] The 4-methyl-1-pentene polymer (A) may further satisfy one or more of the following requirements (d) to (g), and more preferably satisfies two or more of the following requirements (d) to (g).

[0028] [Requirement (d)] The 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. by the method described in the examples described later, of preferably 0.5 to 6.0 dL / g, more preferably 0.65 to 5.6 dL / g, and further preferably 0.8 to 5.4 dL / g. The 4-methyl-1-pentene polymer (A) having an intrinsic viscosity [η] within the above range has good heat resistance. Therefore, the resin layer formed from the coating agent obtained from the composition containing the 4-methyl-1-pentene polymer (A) having an intrinsic viscosity [η] within the above range also tends to have good heat resistance, and the laminate of the present invention has excellent appearance after heat sealing. In addition, the coating agent obtained by dissolving the composition containing the 4-methyl-1-pentene polymer (A) having an intrinsic viscosity [η] within the above range has good coatability and is suitable for forming the resin layer (II). The intrinsic viscosity [η] can be adjusted, for example, by the amount of hydrogen added in the polymerization step for producing the 4-methyl-1-pentene polymer (A).

[0029] [Requirement (e)] In the 4-methyl-1-pentene polymer (A), if a structural unit derived from 4-methyl-1-pentene is defined as a "structural unit (i)" and a structural unit derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is defined as a "structural unit (ii)", the 4-methyl-1-pentene polymer (A) preferably satisfies the following (e1) and (e2). (e1) The amount (U1) of the structural unit (i) in the 4-methyl-1-pentene polymer (A) is preferably 84 to 100 mol %, more preferably 87 to 99.0 mol %, and even more preferably 90 to 98.5 mol % (wherein the total of the structural units (i) and (ii) is 100 mol %). (e2) The amount (U2) of the structural unit (ii) in the 4-methyl-1-pentene polymer (A) is preferably 0 to 16 mol %, more preferably 1.0 to 13 mol %, and even more preferably 1.5 to 10 mol % (wherein the total of the structural units (i) and (ii) is 100 mol %). Incidentally, U1 and U2 are determined by the method described in the Examples. The 4-methyl-1-pentene polymer (A) having U1 and U2 in the above ranges is excellent in heat resistance. Therefore, the resin layer formed using the coating agent obtained from the composition containing the 4-methyl-1-pentene polymer (A) having U1 and U2 in the above ranges also tends to be excellent in heat resistance, and the laminate of the present invention has excellent appearance after heat sealing.

[0030] The α-olefin from which the structural unit (ii) is derived may be a linear α-olefin. Examples of the α-olefin from which the structural unit (ii) is derived include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, from the viewpoint of heat resistance, α-olefins having 6 to 18 carbon atoms are preferred, and linear α-olefins having 6 to 18 carbon atoms are more preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and the like are preferred, and among these, 1-decene, 1-hexadecene, and 1-octadecene are particularly preferred. The structural unit (ii) may be derived from only one selected from the group consisting of ethylene or α-olefins having 3 to 20 carbon atoms, or may be derived from two or more selected from the group consisting of ethylene or α-olefins having 3 to 20 carbon atoms.

[0031] Here, the 4-methyl-1-pentene polymer (A) may be a copolymer consisting of only the structural unit (i) and the structural unit (ii), in which case the total of the structural unit (i) and the structural unit (ii) is 100 mol %.

[0032] The 4-methyl-1-pentene polymer (A) may further contain, in addition to the structural units (i) and (ii), structural units derived from other polymerizable monomers other than 4-methyl-1-pentene, ethylene, and an α-olefin having 3 to 20 carbon atoms, as long as the amount is small enough not to impair the object of the present invention, specifically 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less. The constituent units derived from other polymerizable monomers contained in the 4-methyl-1-pentene polymer (A) may be of one type or of two or more types. The 4-methyl-1-pentene, ethylene, and α-olefins having 3 to 20 carbon atoms, as well as other polymerizable monomers, may be derived from fossil raw materials or biomass raw materials.

[0033] Specific preferred examples of such other polymerizable monomers include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, and the like. Examples of non-conjugated polyenes include dienes, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.

[0034] Here, when the 4-methyl-1-pentene polymer (A) contains a structural unit derived from another polymerizable monomer, it is preferable that the total content of the structural unit (ii) and the structural unit derived from the other polymerizable monomer is within the range of the content of the structural unit (ii).In this case, the total of the structural unit (i), the structural unit (ii), and the structural unit derived from the other polymerizable monomer is 100 mol%.

[0035] [Requirement (f)] The 4-methyl-1-pentene polymer (A) is preferably a polymer modified with a functional group. When the 4-methyl-1-pentene polymer (A) is modified, the 4-methyl-1-pentene polymer (A) is preferably a graft modified polymer.

[0036] When modifying the 4-methyl-1-pentene polymer (A), an ethylenically unsaturated monomer having a functional group is used. The ethylenically unsaturated monomer used for modification is preferably an unsaturated carboxylic acid and / or a derivative thereof. Examples of the unsaturated carboxylic acid and / or a derivative thereof include an unsaturated compound having one or more carboxylic acid groups, an ester of a compound having a carboxylic acid group and an alkyl alcohol, and an unsaturated compound having one or more carboxylic acid anhydride groups.

[0037] Examples of the unsaturated group of the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The unsaturated carboxylic acid and / or its derivative can be used alone or in combination of two or more. Among these ethylenically unsaturated monomers, unsaturated dicarboxylic acids or their acid anhydrides are preferred, and maleic acid, nadic acid, or their acid anhydrides are particularly preferred.

[0038] The method for graft-modifying the 4-methyl-1-pentene polymer (A) with an ethylenically unsaturated monomer is not particularly limited, and any conventionally known graft polymerization method such as a solution method, a melt kneading method, etc., can be used. For example, there is a method in which the 4-methyl-1-pentene polymer (A) is melted and an ethylenically unsaturated monomer is added to perform graft modification, or a method in which the 4-methyl-1-pentene polymer (A) is dissolved in a solvent to form a solution and an ethylenically unsaturated monomer is added thereto to perform graft modification.

[0039] When the 4-methyl-1-pentene polymer (A) is graft-modified, the amount of graft modification is preferably 0.1 to 5.0 mass%, more preferably 0.4 to 3.0 mass%, and further preferably 0.8 to 2.0 mass%, relative to 100 mass% of the mass of the modified 4-methyl-1-pentene polymer (A). When the amount of graft modification of the 4-methyl-1-pentene polymer (A) is within the above range, the adhesion between the resin layer (II) and the layers (I) and (III) tends to be excellent.

[0040] [Requirement (g)] The crystallization temperature (Tc) determined by a differential scanning calorimeter (DSC) according to the method described in the Examples below is preferably 110 to 220° C., more preferably 120 to 210° C., and further preferably 130 to 200° C. The crystallization temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing the 4-methyl-1-pentene polymer (A) and controlling the content of the structural unit (ii). The 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range is preferable from the viewpoint of heat resistance. Moreover, a coating agent or the like obtained from a composition containing the 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range tends to have good properties and storage stability.

[0041] [Method for producing 4-methyl-1-pentene polymer (A)] The 4-methyl-1-pentene polymer (A) can be obtained by polymerizing 4-methyl-1-pentene, a specific olefin from which the above-mentioned structural unit (ii) is derived, and further, if necessary, the above-mentioned other polymerizable monomer, in the presence of an olefin polymerization catalyst, by a known method.

[0042] Examples of olefin polymerization catalysts that can be used in the production of the 4-methyl-1-pentene polymer (A) include metallocene catalysts.Preferred metallocene catalysts include those described in WO 01 / 53369, WO 01 / 27124, JP-A 3-193796, JP-A 02-41303, WO 06 / 025540, or WO 2014 / 123212.

[0043] The 4-methyl-1-pentene polymer (A) may be a 4-methyl-1-pentene polymer (A) prepared so as to satisfy the requirements (a) to (c) by heat-treating a 4-methyl-1-pentene polymer once produced using the catalyst or the like in an extruder, mixer, etc. Alternatively, the 4-methyl-1-pentene polymer (A) may be a 4-methyl-1-pentene polymer (A) prepared so as to satisfy the requirements (a) to (c) by heat-treating a commercially available 4-methyl-1-pentene polymer (e.g., TPX manufactured by Mitsui Chemicals, Inc.) in an extruder, mixer, etc.

[0044] [Composition (X)] The resin layer (II) is preferably formed from a composition (X) containing a 4-methyl-1-pentene polymer (A). The composition (X) contains the 4-methyl-1-pentene polymer (A) and optionally further contains other components such as an isocyanate compound (B). That is, the resin layer (II) further contains other components such as an isocyanate compound (B) in addition to the 4-methyl-1-pentene polymer (A).

[0045] The content of the 4-methyl-1-pentene polymer (A) in the composition (X) is preferably 50 to 100 mass%, more preferably 60 to 100 mass%, and further preferably 70 to 100 mass%. When the content of the 4-methyl-1-pentene polymer (A) in the composition (X) is within the above range, the laminate of the present invention has excellent printability, heat sealability, and heat resistance, and has excellent appearance after heat sealing.

[0046] [Isocyanate compound (B)] The composition (X) may contain an isocyanate compound (B). The isocyanate compound (B) is not particularly limited as long as it is a compound having an isocyanate group, but from the viewpoint of improving the adhesion between the resin layer (II) and the layer (I) and layer (III), it is preferable that the isocyanate compound (B) is a polyfunctional isocyanate compound having two or more isocyanate groups in one molecule.

[0047] Examples of bifunctional isocyanate compounds having two isocyanate groups in one molecule include aliphatic diisocyanates such as methylene diisocyanate, dimethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dipropyl ether diisocyanate, 2,2-dimethylpentane diisocyanate, 3-methoxyhexane diisocyanate, octamethylene diisocyanate, 2,2,4-trimethylpentane diisocyanate, nonamethylene diisocyanate, decamethylene diisocyanate, 3-butoxyhexane diisocyanate, 1,4-butylene glycol dipropyl ether diisocyanate, and thiodihexyl diisocyanate; Aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, dimethylbenzene diisocyanate, ethylbenzene diisocyanate, isopropylbenzene diisocyanate, tolidine diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 2,7-naphthalene diisocyanate, metaxylylene diisocyanate, paraxylylene diisocyanate, and tetramethylxylylene diisocyanate; and Examples of the diisocyanate include alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.

[0048] The isocyanate compound (B) may be a biuret or isocyanurate, which is a trimer of a difunctional isocyanate compound, an adduct between a polyol such as trimethylolpropane and a difunctional isocyanate compound (i.e., an adduct), or an adduct between an alcohol such as methanol and a difunctional isocyanate compound (i.e., an allophanate).

[0049] Among these, from the viewpoint of preventing discoloration of the laminate, the isocyanate compound (B) is preferably an aliphatic isocyanate compound, more preferably an aliphatic isocyanate compound having two or more isocyanate groups in one molecule, further preferably an aliphatic diisocyanate, an isocyanurate of an aliphatic diisocyanate, an allophanate of an aliphatic diisocyanate and an alcohol, or an adduct of an aliphatic diisocyanate and a polyol, and particularly preferably an aliphatic diisocyanate or an isocyanurate of an aliphatic diisocyanate.

[0050] The isocyanate compound (B) may be a commercially available product. Examples of commercially available products include the Takenate series, such as Takenate D103H, D204, D160N, D170N, D165N, D178NL, D110N, and D370N (manufactured by Mitsui Chemicals, Inc.), and Coronate HX, HXR, HXL, HXLV, HK, HK-T, HL, and 2096 (manufactured by Nippon Polyurethane Industry Co., Ltd.).

[0051] When the composition (X) contains an isocyanate compound (B), the content is preferably 2.00 parts by mass or less, more preferably 1.50 parts by mass or less, based on 100 parts by mass of the 4-methyl-1-pentene polymer (A). When the composition (X) contains an isocyanate compound (B), the lower limit of the content of the isocyanate compound (B) is not particularly limited, but is, for example, 0.001 parts by mass or more based on 100 parts by mass of the 4-methyl-1-pentene polymer (A). The isocyanate compound (B) may be contained in the composition (X) either alone or in combination of two or more.

[0052] [Other components contained in composition (X)] Composition (X) may further contain, as necessary, antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, leveling agents, reinforcing agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, fillers, etc. The resin layer (II) formed from composition (X) may also contain other components contained in composition (X). The amount of the other components may be any amount that does not impair the object of the present invention, but the total amount of the other components is, for example, 0.005 to 5 parts by mass, and preferably 0.01 to 3 parts by mass, relative to 100 parts by mass of the composition (X).

[0053] As the antioxidant, known antioxidants can be used, specifically, hindered phenol compounds, sulfur-based antioxidants, lactone-based antioxidants, organic phosphite compounds, organic phosphonite compounds, or combinations of several of these can be used.

[0054] Examples of the lubricant include sodium, calcium, and magnesium salts of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, and stearic acid, which can be used alone or in combination of two or more. The amount of such a lubricant to be added is, for example, 0.01 to 3 parts by mass, and preferably about 0.1 to 2 parts by mass, relative to 100 parts by mass of the composition (X).

[0055] As the slip agent, it is preferable to use amides of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, stearic acid, erucic acid, and hebenic acid, or bisamides of these saturated or unsaturated fatty acids. Among these, erucic acid amide and ethylene bisstearamide are particularly preferable. It is preferable to mix these fatty acid amides in the range of 0.01 to 5 parts by mass with respect to 100 parts by mass of the 4-methyl-1-pentene polymer (A).

[0056] Examples of the antiblocking agent include finely divided silica, finely divided aluminum oxide, finely divided clay, powdered or liquid silicone resin, tetrafluoroethylene resin, finely divided crosslinked resin, such as crosslinked acrylic or methacrylic resin powder, etc. Among these, finely divided silica and crosslinked acrylic or methacrylic resin powder are preferred.

[0057] In addition, when the resin layer (II) is formed using a coating agent in which the composition (X) is dissolved, as described below, it is also a preferred embodiment to add a leveling agent to the composition (X). As a leveling agent for reducing the surface roughness of the resin layer (II) formed using the coating agent, a fluorine-based nonionic surfactant, a special acrylic resin-based leveling agent, a silicone-based leveling agent, etc. can be used, and those having good compatibility with the solvent are preferred, and the amount added is in the range of 1 to 50,000 ppm relative to the 4-methyl-1-pentene polymer (A) in the composition (X).

[0058] As the reinforcing agent, for example, 5 to 50 parts by mass of metal oxides such as silicon, titanium, aluminum, and zirconium, polyfunctional alkoxy compounds or oligomers thereof, and clay minerals can be blended with 100 parts by mass of the 4-methyl-1-pentene polymer (A) in the composition (X), and the hardness and elastic modulus of the resin layer (II) formed from the composition (X) can be increased. If the amount added is less than 5 parts by mass, the effect is too low, and if it exceeds 50 parts by mass, the transparency or mechanical strength of the resin layer (II) may be impaired.

[0059] [Method for producing composition (X)] The composition (X) can be produced by mixing the 4-methyl-1-pentene polymer (A) with other components such as the isocyanate compound (B). Alternatively, instead of producing the composition (X) itself, a coating agent containing the composition (X) dissolved therein may be produced by dissolving all the components contained in the composition (X) in a solvent, and the coating agent may be dried to produce the composition (X).

[0060] [Thickness of resin layer (II)] From the viewpoint of suppressing curling in the obtained laminate, the thickness of the resin layer (II) is preferably 50 μm or less, more preferably 46 μm or less, further preferably 0.01 to 46 μm, and particularly preferably 0.05 to 46 μm. When the resin layer (II) is formed using a coating agent in which the composition (X) is dissolved, the thickness of the resin layer (II) can be made thinner. In this case, the thickness of the resin layer (II) is, for example, 20 μm or less, preferably 10 μm or less, more preferably 0.01 to 8 μm, and even more preferably 0.05 to 5 μm. The thickness of the resin layer (II) can be adjusted, for example, by the concentration of the 4-methyl-1-pentene polymer (A) in the coating agent used to form the resin layer (II). The lower the concentration of the 4-methyl-1-pentene polymer (A) contained in the coating agent, the thinner the thickness of the resulting resin layer (II) tends to be.

[0061] <Layer (I) and Layer (III)> Both the layer (I) and the layer (III) contain a thermoplastic resin. The thermoplastic resins contained in the layer (I) and the layer (III) may be the same as or different from each other. The layer (I) and the layer (III) may be a single layer or a multi-layer. The layer (I) and the layer (III) may be a film containing a polyolefin having a melting point of 200° C. or less, or may be a molded product such as a bottle molded by a known method such as injection molding or blow molding of the polyolefin. The layer (I) and the layer (III) may be a layer laminated to paper, nonwoven fabric, metal, or a gas barrier layer described later.

[0062] As the thermoplastic resin, any known thermoplastic resin other than the 4-methyl-1-pentene polymer (A) can be used without any particular limitation. Examples of the thermoplastic resin include olefin polymers, polyamides, polyesters, polyacetals, styrene resins, acrylic resins, polycarbonates, polyphenylene oxides, chlorine resins, vinyl acetate resins, ethylene-(meth)acrylic acid ester copolymers, ethylene-(meth)acrylic acid resins and ionomer resins thereof, vinyl alcohol resins, cellulose resins, thermoplastic elastomers, and various copolymer rubbers.

[0063] The layers (I) and (III) preferably contain a polyolefin having a melting point of 200° C. or less as measured by a differential scanning calorimeter (DSC). The polyolefin having a melting point of 200° C. or less is not particularly limited, and examples thereof include high-density polyethylene, low-density polyethylene, linear low-density polyethylene such as ethylene-α-olefin copolymer, polypropylene, 4-methyl-1-pentene polymers (excluding those corresponding to 4-methyl-1-pentene polymer (A)), polybutene, and the like. "High density polyethylene" refers to polyethylene with a density of 0.940 g / cm 3 It is preferable that the polyethylene is more than 100%. In addition, "low density polyethylene" refers to polyethylene with a density of 0.940 g / cm 3 It is preferable that:

[0064] Among these, the polyolefin having a melting point of 200°C or less is preferably at least one resin selected from the group consisting of polypropylene and polyethylene, more preferably at least one resin selected from the group consisting of polypropylene, low-density polyethylene, and high-density polyethylene, and even more preferably at least one resin selected from the group consisting of polypropylene and low-density polyethylene.

[0065] The method for forming the layer (I) and the layer (III) is not particularly limited and may be a general method such as extrusion, uniaxial or biaxial stretching, etc. The layer (I) and the layer (III) may contain various additives that are usually used in polyolefins, such as a heat stabilizer, a weather stabilizer, an ultraviolet absorber, a lubricant, a slip agent, a nucleating agent, an antiblocking agent, an antistatic agent, an antifogging agent, a pigment, a dye, an inorganic or organic filler, etc., within a range that does not impair the object of the present invention. Furthermore, the layer (I) and the layer (III) may contain a polyolefin having a melting point of more than 200° C. as measured by a differential scanning calorimeter (DSC) without impairing the object of the present invention. The thickness of the layer (I) and the layer (III) is, for example, 10 to 100 μm, but is not particularly limited.

[0066] <Other layers> The laminate of the present invention may have layers other than the above-mentioned layer (I), resin layer (II), and layer (III) (hereinafter, also referred to as "other layers"). Examples of the other layers include a protective layer, a primer layer, a gas barrier layer, and the like. The laminate may be, for example, a laminate in which the layer (I) or the layer (III) is laminated so as to be in contact with a primer layer, and the primer layer side of the layer (I) or the layer (III) is laminated so as to be in contact with the resin layer (II). The laminate may also be a laminate in which a layer selected from the group consisting of paper, nonwoven fabric, metal, and a gas barrier layer is laminated so as to be in contact with the layer (I) or the layer (III). The gas barrier layer is not particularly limited as long as it is a layer that suppresses the permeation of a desired gas, and examples thereof include layers formed of nylon, polyethylene terephthalate, ethylene-vinyl alcohol copolymer, silicon oxide, and the like.

[0067] <Laminate> The laminate of the present invention has the above-mentioned layer (I), resin layer (II), and layer (III) in this order in the thickness direction. The resin layer (II) included in the laminate of the present invention may be one layer or may be two or more layers. For example, the resin layer (II) may be two layers, an intermediate layer and an outer layer, or may be three or more layers including a plurality of intermediate layers and outer layers. The resin layer (II) included in the laminate of the present invention satisfies the above-mentioned requirements of the resin layer (II) even when the resin layer (II) is two or more layers. When the resin layer (II) includes a plurality of layers, these layers may be the same or different. For example, the resin layer (II) may be formed by laminating an intermediate layer including a modified 4-methyl-1-pentene polymer (A) and an outer layer including an unmodified 4-methyl-1-pentene polymer (A) in this order. In one preferred embodiment of the laminate of the present invention, the resin layer (II) has a first surface and a second surface, the layer (I) is provided in contact with the first surface of the layer (II), and the layer (III) is provided in contact with the second surface of the layer (II).

[0068] <<Method for manufacturing laminate>> The method for producing the laminate of the present invention is not particularly limited, and a known production method can be used. For example, the laminate of the present invention can be suitably produced by the following production method. That is, the production method of the laminate of the present invention preferably includes a step (1) of preparing a coating agent in which the composition (X) is dissolved by mixing the 4-methyl-1-pentene polymer (A), the solvent (C), and optionally the isocyanate compound (B) and other components contained in the composition (X), and a step (2) of forming a resin layer (II) by attaching the coating agent to a part or the entire surface of the layer (I) and the layer (III) and removing the solvent (C).

[0069] [Coating agent containing composition (X) dissolved therein] The coating agent in which the composition (X) is dissolved is obtained by dissolving the composition (X) in a solvent (C). Therefore, the coating agent contains the components and solvent contained in the composition (X) used for preparing the coating agent. For example, when the composition (X) contains 100% by mass of the 4-methyl-1-pentene polymer (A), the coating agent is obtained by dissolving the 4-methyl-1-pentene polymer (A) in a solvent (C). In addition, when the composition (X) used for preparing the coating agent contains an isocyanate compound (B) and other components in addition to the 4-methyl-1-pentene polymer (A), the obtained coating agent contains these substances.

[0070] The content of the 4-methyl-1-pentene polymer (A) in the coating agent in which the composition (X) is dissolved is, for example, 0.01 to 50 mass%, preferably 0.05 to 30 mass%, more preferably 0.07 to 25 mass%, even more preferably 0.1 to 20 mass%, particularly preferably 0.2 to 20 mass%, and most preferably 0.3 to 20 mass%. The content of the solvent (C) in the coating agent is, for example, 50 to 99.99 mass%, preferably 70 to 99.95 mass%, more preferably 75 to 99.93 mass%, even more preferably 80 to 99.9 mass%, particularly preferably 80 to 99.8 mass%, and most preferably 80 to 99.7 mass%.

[0071] When the contents of the 4-methyl-1-pentene polymer (A) and the solvent (C) in the coating agent are within the above ranges, a good balance is achieved between the handleability and the ease of removing the solvent when forming the resin layer (II) from the coating agent.

[0072] [Solvent (C)] The solvent (C) is not particularly limited as long as it can dissolve the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B), but an organic solvent can be preferably used. Examples of the solvent (C) include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, cyclohexane, methylcyclohexane, and ethylcyclohexane; aromatic hydrocarbons such as toluene and xylene. Among these, toluene, cyclohexane, and methylcyclohexane can be preferably used.

[0073] [Method for producing a coating agent containing dissolved composition (X)] The method for producing the coating agent in which the composition (X) is dissolved is not particularly limited, and it can be produced by a commonly used method. For example, it can be produced by adding 4-methyl-1-pentene polymer (A) to solvent (C) and stirring for a predetermined time at a temperature below the boiling point of the solvent (C). In addition, the composition (X) can also be produced by heat-treating a separately prepared 4-methyl-1-pentene polymer to prepare a 4-methyl-1-pentene polymer (A), adding the obtained 4-methyl-1-pentene polymer (A) to the solvent (C), and stirring for a predetermined time at a temperature below the boiling point of the solvent (C). When the coating agent contains an isocyanate compound (B), the isocyanate compound (B) may be added to the solvent (C) in which the 4-methyl-1-pentene polymer (A) is dissolved. Also, the isocyanate compound (B) may be added to the solvent (C) before dissolving the 4-methyl-1-pentene polymer (A). In this case, the 4-methyl-1-pentene polymer (A) may be added to the solvent (C) in which the isocyanate compound (B) is dissolved. Furthermore, the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B) may be added to the solvent (C) at the same time. Also, when the coating agent contains the other components other than the 4-methyl-1-pentene polymer (A) and the isocyanate compound (B), the timing at which the other components are added is also arbitrary.

[0074] [Step of forming resin layer (II)] An example of the treatment carried out in the step of forming the resin layer (II) (step (2)) will be described below. In step (2), specifically, a coating agent in which the composition (X) is dissolved is attached to the surface of the layer (I) and the layer (III), and the coating agent is heated to a temperature close to the boiling point of the solvent (C) to remove the solvent (C) in the composition (X) to a certain extent. The method of applying the coating agent is not particularly limited, and examples thereof include application using a brush or a paint brush, spraying, screen printing, flow coating, spin coating, and dipping, and application to a roll or a flat plate using a bar coater, a T-die, a T-die with a bar, a doctor knife, a roll coater, a die coater, etc. The dipping method includes a method of immersing one side of the layer (I) and the layer (III) in a coating agent, a method of immersing both sides of the layer (I) and the layer (III) in a coating agent, and a method of adhering the coating agent to both sides of the layer (I) and the layer (III) by holding the layer (I) and the layer (III) for a predetermined period of time while immersing one side of the layer (I) and the layer (III) in the coating agent.

[0075] In the present application, the removal of the solvent does not only mean the complete removal of the solvent (C) from the coating agent, but also includes the removal of the solvent (C) to such an extent that the 4-methyl-1-pentene polymer (A) contained in the coating agent can be formed as the resin layer (II). Specifically, the removal of the solvent includes the removal of the solvent until the solvent is about 0.001 to 0.5 mass% relative to 100% by mass of the resin layer (II) produced using the composition (X). The method for removing the solvent is not particularly limited, and the solvent may be dried by leaving it alone, but is generally removed by heating and drying at 30 to 220°C. In addition, in order to prevent thermal deterioration or thermal decomposition of the 4-methyl-1-pentene polymer (A), it is preferable to remove the solvent (C) at a temperature equal to or lower than the melting point (Tm) of the 4-methyl-1-pentene polymer (A). On the other hand, if the drying temperature is too low, the drying time will be long, which will deteriorate productivity, and if the drying temperature is too high, problems such as foaming and deterioration will occur. In order to dry in a short time while preventing foaming, the temperature may be increased in two or more stages or continuously while drying. In addition, the amount of solvent remaining in the resin layer (II) can be reduced by immersing the resin layer (II) in a solvent in which the 4-methyl-1-pentene polymer (A) is poorly soluble, such as water, methanol, ethanol, acetone, or methylene chloride, or by exposing the resin layer (II) to a vapor atmosphere of the solvent, after the drying step. The amount of solvent remaining in the resin layer (II) after drying is, for example, 0.5% by mass or less, preferably 0.05% by mass or less, and more preferably 0.01% by mass or less.

[0076] In addition to the above-mentioned methods, other methods for producing the laminate of the present invention include, for example, a method in which another film is laminated on a film previously obtained by T-die molding or inflation molding, etc., by a known lamination method such as extrusion lamination or extrusion coating, and a method in which multiple films are molded independently and then each film is laminated by dry lamination. From the standpoint of productivity, etc., co-extrusion molding in which the components forming each layer are fed into a multilayer extruder and molded is preferred. When forming a laminate by the co-extrusion molding, for example, the components forming each layer (eg, pellets of a resin composition) are melt-extruded at a cylinder temperature usually in the range of 180 to 300°C.

[0077] <Applications of laminate> When the layer (I) and the layer (III) are laminated to paper, for example, polyolefin having a melting point of 200° C. or less, the laminate of the present invention is suitably used as various process papers such as release paper, photographic paper, and tape separator. For example, there are uses such as release paper for synthetic leather, process paper for rubber manufacturing, release paper for urethane curing, release paper for epoxy curing, process paper for solar cell manufacturing, process paper for semiconductor manufacturing, process paper for fuel cell manufacturing, process paper for electric and electronic parts manufacturing, process paper for semiconductor product manufacturing, process paper for circuit board manufacturing, release paper for flexible printed circuit boards, release paper for rigid boards, release paper for rigid flexible boards, process paper for advanced composite material manufacturing, release paper for carbon fiber composite curing, release paper for glass fiber composite curing, release paper for aramid fiber composite curing, release paper for nanocomposite curing, release paper for filler filler curing, heat-resistant and water-resistant photographic paper, OA paper, adhesive tape separator, silicon tape separator, adhesive separator, etc.

[0078] Since the laminate of the present invention has excellent heat resistance as described above, when a resin film (preferably a polyolefin having a melting point of 200° C. or less) is used as Layer (I) and Layer (III), the laminate is also suitably used as a protective film for various display devices, semiconductor devices, optical members, printed circuit boards, capacitors, etc., daily necessities packaging materials, food packaging materials, food containers, retort containers, protective films, decorative films and sheets, shrink films, infusion bags, heat-sealing films, medical containers, release films or release layers of release films, etc.

[0079] Among these, the laminate of the present invention is particularly suitable for use as a packaging film. When the laminate of the present invention is used as a packaging film, a packaging film having excellent appearance even after heat sealing can be easily obtained. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0081] <Method of measuring physical properties of polymer> [composition] The amount of structural units (i) (the amount of structural units derived from 4-methyl-1-pentene, U1) and the amount of structural units (ii) (the amount of structural units derived from α-olefin, U2) in the 4-methyl-1-pentene polymer (A) were determined by the following apparatus and under the following conditions: 13 Calculated from C-NMR spectrum.

[0082] The ECP500 nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. was used. The solvent was a mixture of o-dichlorobenzene / heavy benzene (80 / 20% by volume), the sample concentration was 55 mg / 0.6 mL, the measurement temperature was 120°C, and the observed nuclei were 13 The measurements were performed using C (125 MHz), a sequence of single pulse proton decoupling, a pulse width of 4.7 μs (45° pulse), a repetition time of 5.5 s, and an accumulation count of 10,000 or more, with 27.50 ppm as the reference value for the chemical shift. 13 The compositions of 4-methyl-1-pentene and α-olefins were quantified by C-NMR spectroscopy. The amounts of the structural units (i) and (ii) were determined in the same manner for the 4-methyl-1-pentene polymer used in the comparative examples described below.

[0083] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. That is, about 20 mg of the 4-methyl-1-pentene polymer (A) as a sample was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0) The intrinsic viscosity [η] of the 4-methyl-1-pentene polymer used in the comparative example described later was also determined in the same manner.

[0084] [Grafting amount] When the 4-methyl-1-pentene polymer (A) was graft-modified, the amount of graft modification (i.e., the content of the structural units derived from the ethylenically unsaturated monomer used for modification when the mass of the modified 4-methyl-1-pentene polymer (A) was taken as 100% by mass) was determined by the following method. First, a sample of 4-methyl-1-pentene polymer (A) was treated at 250°C, preheated for 5 minutes, and pressed for 3 minutes to prepare a pressed film, and the pressed film was subjected to IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (FT-IR410, manufactured by JASCO Corporation). In the following examples, maleic anhydride was used for graft modification, and therefore the peak at 1860 cm ‐1 and 4321 cm -1 The amount of graft modification was calculated from the peak intensity.

[0085] [Melting point (Tm), endothermic end temperature (TmE), exothermic onset temperature (TcS), and crystallization temperature (Tc)] Using a differential scanning calorimeter (DSC) measuring device (model: DSC220C) manufactured by Seiko Instruments Inc., an exothermic-endothermic curve was obtained in accordance with ASTM D3418, and the melting point (Tm) and crystallization temperature (Tc) were calculated as follows.

[0086] Approximately 5 mg of the sample was placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, cooled to 20°C at a cooling rate of 10°C / min, held at 20°C for 5 minutes, and then heated again from 20°C to 280°C at a heating rate of 10°C / min. The crystallization peak that appeared during the first cooling was taken as the crystallization temperature (Tc). When multiple crystallization peaks were detected, the one with the highest temperature was taken as the crystallization temperature (Tc). The melting peak that appeared during the second heating was taken as the melting point (Tm). When multiple melting peaks were detected, the one with the highest temperature was taken as the melting point (Tm).

[0087] The temperature at which the endotherm of the melting (endotherm) curve ended was taken as the endotherm end temperature (TmE), and the temperature at which the heat generation of the crystallization (exotherm) curve started was taken as the exotherm start temperature (TcS).

[0088] The start and end points are the points at which it can be confirmed that the curve deviates from the baseline where the amount of heat becomes constant at the start or end of endothermic or exothermic reaction, and a difference in the amount of heat begins to appear.

[0089] <Preparation Example 1: Preparation of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride> Using the method described in Preliminary Experiment 5 (paragraphs

[0346] to

[0348] ) of WO 2014 / 123212, (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride was synthesized.

[0090] <Production Example 1: Production of Polymer 1> 500 mL of 4-methyl-1-pentene and 220 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 30 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing 0.039 mmol of liquid methylaluminoxane in terms of aluminum atom and 0.00013 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 10 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 1. The obtained polymer 1 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 1 was found to be 94.1 mol% derived from 4-methyl-1-pentene and 5.9 mol% derived from α-olefin. The melting point (Tm) of polymer 1 was 190°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.3 dL / g. Other physical properties of polymer 1 are shown in Table 1.

[0091] <Production Example 2: Production of Polymer 2> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 20 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing liquid methylaluminoxane at 0.033 mmol in terms of aluminum atom and further containing 0.00011 mmol of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 13 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 2. The obtained polymer 2 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 2 was found to be 97.6 mol% of structural units derived from 4-methyl-1-pentene, and 2.4 mol% of the total of structural units derived from α-olefins. The melting point (Tm) of polymer 2 was 207°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.4 dL / g. Other physical properties of polymer 2 are shown in Table 1.

[0092] <Production Example 3: Production of Polymer 3> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen, at 23°C. 15 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged, and the autoclave was heated to an internal temperature of 60°C. Thereafter, 2 mL of a toluene solution containing 0.06 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.0002 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was injected into the autoclave under pressure with nitrogen to initiate polymerization. During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 30 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate polymer 3. The obtained polymer 3 was dried at 130°C under reduced pressure for 10 hours. The content of structural units in polymer 3 was found to be 96.7 mol% derived from 4-methyl-1-pentene and 3.3 mol% derived from α-olefin. The melting point (Tm) of polymer 3 was 212°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 2.3 dL / g. Other physical properties of polymer 3 are shown in Table 1.

[0093] <Production Example 4: Production of Polymer 4> [Synthesis Example 4-1: Production of olefin polymerization catalyst] At 30°C, in a three-neck flask equipped with a 200 mL stirrer that had been thoroughly substituted with nitrogen, 30 mL of purified decane and 14.65 mmol of particulate solid polymethylaluminoxane (synthesized using the method described in International Publication No. 2014 / 123212) having a median diameter D50 of 28 μm in volumetric statistics and an aluminum atom content of 43 mass% were charged under a nitrogen stream to form a suspension. 50.0 mg (0.0586 mmol) of the transition metal compound (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene)) zirconium dichloride obtained in Preparation Example 1 was added to the suspension as a 4.58 mmol / L toluene solution while stirring. After 1 hour, stirring was stopped, and the resulting mixture was washed with 100 mL of decane by decantation, after which decane was added to make 50 mL of a slurry (zirconium atom loading rate: 98%). Note that the "zirconium atom loading rate" refers to the proportion (by mass) of zirconium atoms loaded on the solid catalyst component out of the zirconium atoms in the added transition metal compound.

[0094] [Synthesis Example 4-2: Preparation of prepolymerization catalyst component] To the slurry liquid prepared in Synthesis Example 4-1, 1.0 mL of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atom) was charged under a nitrogen gas flow at 25°C. After cooling to 15°C, 10 mL of 4-methyl-1-pentene was charged into the reactor over 60 minutes. The start of the charging of 4-methyl-1-pentene was regarded as the start of prepolymerization. Stirring was stopped 2.0 hours after the start of prepolymerization, and the resulting mixture was washed three times with 100 mL of decane by decantation. The prepolymerization catalyst component was a decane slurry (9.5 g / L, 0.56 mmol / L in terms of zirconium atom).

[0095] [Preparation of Polymer 4a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol in terms of zirconium atoms of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged. 23.75 NmL of hydrogen was charged, and then a mixture of 230 mL of 4-methyl-1-pentene and 22.4 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charging of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain polymer 4a. The yield was 142 g. The content of structural units in polymer 4a was found to be 96.5 mol% derived from 4-methyl-1-pentene, and 3.5 mol% in total derived from α-olefins. Polymer 4a had a melting point (Tm) of 201°C and a limiting viscosity [η] (in decalin at 135°C) of 4.2 dL / g.

[0096] [Production of Polymer 4] Polymer 4a was mixed with 0.02 phr of the phenolic stabilizer Irganox 1010 (manufactured by BASF Chiba) as a heat stabilizer, and the mixture was kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain Polymer 4. The amount of the structural units in polymer 4 was the same as that of polymer 4a. The melting point (Tm) of polymer 4 was 201° C., and the intrinsic viscosity [η] (in decalin at 135° C.) was 1.0 dL / g. Other physical properties of polymer 4 are shown in Table 1.

[0097] <Production Example 5: Production of Polymer 5> [Preparation of Polymer 5a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.0020 mmol of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged in terms of zirconium atoms. 16.25 NmL of hydrogen was charged, and then a mixture of 231 mL of 4-methyl-1-pentene and 20.6 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charge of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. One hour and two hours after the start of polymerization, 16.25 NmL of hydrogen was charged. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain polymer 5a. The yield was 128 g. The content of structural units in polymer 5a was 97.0 mol% derived from 4-methyl-1-pentene, and the total content of structural units derived from α-olefins was 3.0 mol%. Polymer 5a had a melting point (Tm) of 203°C and a limiting viscosity [η] (in decalin at 135°C) of 5.3 dL / g.

[0098] [Production of Polymer 5] Polymer 5a (100 parts by mass), 2 parts by mass of maleic anhydride, and 0.02 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (Perhexyne 25B, manufactured by NOF Corporation) as an organic peroxide were blended and kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain Polymer 5. The amount of the structural units in polymer 5 was the same as that of polymer 5a. The melting point (Tm) of polymer 5 was 203° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.8 dL / g, and the graft amount was 1.5 mass%. Other physical properties of polymer 5 are shown in Table 1.

[0099] <Production Example 6: Production of Polymer 6> Polymer 6 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 4a was used instead of Polymer 5a. The amount of the structural unit in polymer 6 was the same as that of polymer 4a. The melting point (Tm) of polymer 6 was 201° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.9 dL / g, and the graft amount was 1.5 mass%. Other physical properties of polymer 6 are shown in Table 1.

[0100] <Production Example 7: Production of Polymer 7> [Preparation of polymer 7a] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol of the decane slurry of the prepolymerization catalyst component of Synthesis Example 4-2 was charged in terms of zirconium atoms. 23.75 NmL of hydrogen was charged, and then a mixture of 232 mL of 4-methyl-1-pentene and 19.6 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of the charge of the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried at 80°C under reduced pressure for 8 hours to obtain polymer 7a. The yield was 146 g. The content of structural units in polymer 7a was 96.7 mol% derived from 4-methyl-1-pentene, and the total content of structural units derived from α-olefins was 3.3 mol%. Polymer 7a had a melting point (Tm) of 203°C and a limiting viscosity [η] (in decalin at 135°C) of 4.0 dL / g.

[0101] [Production of Polymer 7] Polymer 7 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 7a was used instead of Polymer 5a. The amount of the structural units in polymer 7 was the same as that of polymer 7a. The melting point (Tm) of polymer 7 was 203° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.9 dL / g, and the graft amount was 1.6 mass%. Other physical properties of polymer 7 are shown in Table 1.

[0102] <Production Example 8: Production of Polymer 8> Polymer 8 was obtained by carrying out the same production process as for Polymer 5, except that Polymer 3 was used instead of Polymer 5a. The amount of the structural units in polymer 8 was the same as that in polymer 3. The melting point (Tm) of polymer 8 was 210° C., the intrinsic viscosity [η] (in decalin at 135° C.) was 0.8 dL / g, and the graft amount was 1.5 mass%. Other physical properties of polymer 8 are shown in Table 1.

[0103] [Table 1]

[0104] [Preparation of Layer (I) and Layer (III) (Resin Film)] A cast film (resin film I-1) having a thickness of 100 μm was obtained by forming polypropylene (Prime Polymer Co., Ltd., brand: F113G) into a film using a cast film forming machine with a T-die at a cylinder temperature of 230° C. The obtained cast film was subjected to a corona treatment and used as layer (I) or layer (III). A cast film (resin film I-2) having a thickness of 100 μm was obtained in the same manner as for resin film I-1, except that polypropylene was changed to low-density polyethylene (manufactured by Prime Polymer Co., Ltd., brand: SP0540) and the film was molded at a cylinder temperature of 200° C. The obtained cast film was subjected to a corona treatment and used as layer (I) or layer (III).

[0105] <Preparation Example 2: Preparation of a coating agent by dissolving composition (X1)> To 10 g of polymer 1 (i.e., the mass of polymer 1 is taken as 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration became 5% by mass. The mixture was stirred at 200 rpm for 1 hour at 90°C to produce a coating agent in which a composition (X1) containing polymer 1 was dissolved.

[0106] <Preparation Example 3: Preparation of a coating agent containing composition (X2) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 2 was used instead of Polymer 1.

[0107] <Preparation Example 4: Preparation of a coating agent containing composition (X3) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 3 was used instead of Polymer 1.

[0108] <Preparation Example 5: Preparation of a coating agent containing composition (X4) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 2, except that Polymer 4 was used instead of Polymer 1.

[0109] <Preparation Example 6: Preparation of a coating agent containing composition (X5) dissolved therein> For 10 g of polymer 5 (i.e., the mass of polymer 5 is 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 5% by mass, and the mixture was stirred at 90°C for 1 hour at 200 rpm. After cooling to 23°C, 0.01% by mass of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) was added and stirred at 200 rpm for 5 minutes to produce a coating agent in which a composition (X5) containing polymer 5 was dissolved.

[0110] <Preparation Example 7: Preparation of a coating agent containing composition (X6) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 6 was used instead of Polymer 5.

[0111] <Preparation Example 8: Preparation of a coating agent containing composition (X7) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 7 was used instead of Polymer 5.

[0112] <Preparation Example 9: Preparation of a coating agent containing composition (X8) dissolved therein> A coating agent was prepared in the same manner as in Preparation Example 6, except that Polymer 8 was used instead of Polymer 5.

[0113] <Example 1> [Preparation of Laminate] The settings of the applicator were adjusted so that the thickness of the resin layer (II) formed from the composition (X5) prepared above was 0.1 μm after drying on the corona-treated surface of the resin film I-1 to be the layer (I), and the coating agent in which the composition (X5) was dissolved was applied at 23 ° C. and uniformly spread with the applicator. Next, the corona-treated surface of the resin film I-1 to be the layer (III) was faced toward the resin layer (II) side, and the two were laminated by rolling back and forth once with a 2 kg roller. The laminate was dried at 100 ° C. for 20 seconds and aged at 80 ° C. for 20 hours to obtain a laminate having the layer (I), the resin layer (II), and the layer (III).

[0114] [Appearance evaluation after heat sealing] Two test pieces, each 150 mm long and 30 mm wide, were obtained from the laminate obtained above. The two test pieces obtained were overlapped with the layers (III) facing each other, and heat sealed for 0.6 seconds using a heat sealer at a gauge pressure of 0.1 MPa under the conditions of a temperature of 180°C for the upper surface of the heat seal bar and room temperature for the lower surface, and the appearance was evaluated. [Evaluation Criteria] A: No change in appearance after heat sealing B: Wrinkles appear on the surface after heat sealing

[0115] <Examples 2 to 12> The laminate was produced and its physical properties were evaluated in the same manner as in Example 1, except that the types of layer (I) and layer (III) and the type and thickness of resin layer (II) were changed as shown in Table 2. The results are shown in Table 2.

[0116] <Example 13> The laminate was produced using a three-type, three-layer T-die sheet molding machine (manufactured by Thermo Plastics Industries Co., Ltd.) equipped with a T-die with a lip width of 330 mm, three hopper inlets, and a 30 mmφ screw. Polymer 5 was placed in the first hopper, and the cylinder temperature was set to 270°C. Polypropylene (Prime Polymer Co., Ltd., Prime Polypro F113G, MFR (230°C, 2.16 kg load): 3.0 g / 10 min) was placed in the second hopper, and the cylinder temperature for these hoppers was set to 230°C. Low-density polyethylene (Prime Polymer Co., Ltd., brand: SP0540) was placed in the third hopper, and the cylinder temperature for these hoppers was set to 200°C. The die temperature was set to 270°C, and the molten mixture of polymer 5, polypropylene, and low-density polyethylene was extruded from the T-die as a multilayer film. The film was then pulled up at a take-up speed of 2.5 m / min while being pressed against a metal cooling roll controlled at 80°C by air pressure, thereby obtaining a laminate having layers (I), (II), and (III) that was cooled and solidified to a thickness of 150 μm. The physical properties of the laminate obtained above were evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0117] <Examples 14 to 24> The laminate was produced and its physical properties were evaluated in the same manner as in Example 13, except that the types of layer (I) and layer (III) and the type and thickness of resin layer (II) were changed as shown in Table 3. The results are shown in Table 3.

[0118] <Comparative Example 1> The physical properties of the resin film I-1 were evaluated without any modification, and the results are shown in Table 4.

[0119] <Comparative Example 2> The physical properties of the resin film I-2 were evaluated without any modification, and the results are shown in Table 4.

[0120] [Table 2]

[0121] [Table 3]

[0122]

Table 4

Claims

1. A layer (I) containing a thermoplastic resin; a resin layer (II) containing a 4-methyl-1-pentene polymer (A) satisfying the following requirements (a) to (c); A layer (III) containing a thermoplastic resin; A laminate having the above in this order in the thickness direction. (a) The melting point (Tm) measured by differential scanning calorimetry (DSC) is 180 to 220°C. (b) The endothermic end temperature (TmE) in the melting (endothermic) curve measured by DSC is 230° C. or lower. (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by DSC is 210° C. or lower.

2. The laminate according to claim 1, wherein the layer (II) has a first surface and a second surface, the layer (I) is provided in contact with the first surface of the layer (II), and the layer (III) is provided in contact with the second surface of the layer (II).

3. The laminate according to claim 1 , wherein the layer (I) and the layer (III) contain a polyolefin having a melting point of 200° C. or less as measured by differential scanning calorimetry (DSC).

4. 4. The laminate according to claim 3, wherein the polyolefin having a melting point of 200° C. or less is at least one resin selected from the group consisting of polypropylene and polyethylene.

5. 2. The laminate according to claim 1, wherein the 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] measured in decalin at 135° C. in the range of 0.5 to 6.0 dL / g.

6. In the 4-methyl-1-pentene polymer (A), the amount of structural units (U1) derived from 4-methyl-1-pentene is 84 to 100 mol %, 3. The laminate according to claim 1, wherein the total amount (U2) of structural units derived from ethylene or an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 0 to 16 mol % (wherein the sum of U1 and U2 is 100 mol %).

7. 7. The laminate according to claim 6, wherein the α-olefin is an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).

8. The laminate according to claim 1 or 2, wherein the resin layer (II) has a thickness of 50 μm or less.

9. 2. The laminate according to claim 1, wherein the 4-methyl-1-pentene polymer (A) is modified.

10. 10. The laminate according to claim 9, wherein the 4-methyl-1-pentene polymer (A) is a graft modified product, and the amount of graft modification is 0.1 to 5.0% by mass.

11. The laminate according to claim 1 , wherein the resin layer (II) further contains an isocyanate compound (B).

Citation Information

Patent Citations

  • Polypropylene resin composition, film or sheet, stretched film obtained from such film or sheet, multilayer body, and stretched film obtained from such multilayer body

    WO2007015415A1

Cited By

  • JPWO2025205289A1

  • Biaxially-oriented polyolefin film

    WO2025205289A1